Brain Delivery Systems via Mechanism Independent of Receptor-Mediated Endocytosis and Adsorptive-Mediated Endocytosis - Bohn Thomsen, Louiza; Lichota, Jacek; Navndrup Eskehave, Thomas; Linemann, Thomas; Hog Mortensen, Joachim; Gaarn du Jardin, Kristian; Moos, Torben (Current Pharmaceutical Biotechnology, 2012)
The endothelial cells of the brain form the blood-brain barrier (BBB) that denotes a major restraint for drug entry to the brain. Traditional attempts to bypass the BBB have been by formulation of drugs with lipophilicity or low molecular weight designed to enable transport via solute nutrient transporters. The identification of many new targets in the brain cells form new ways of thinking drug design as modern therapeutics could be proteins and molecules of genetic origins like siRNA and cDNA that are prevented from entry into the brain unless encapsulated in drug carriers. In many chronic disorders affecting the central nervous system, the BBB is physically intact which further limits the entry of large molecules. The desirable entry of such molecules will be made by formulation of particular drug carriers that will enable their transport into the brain endothelium, or even through the endothelium and into the brain. This review discusses the potential of different principles for drug therapy to the brain with these main emphases on drug transport through the BBB: i) the effects of molecular lipidization, ii) the involvement of solute nutrient carriers, iii) targeted delivery using small peptides with high membrane penetrating properties, iv) treatment with magnetic nanoparticles. These different principles for therapy are also discussed with focus on possibilities of their improvement for targeted delivery to the brain.
Keywords: central nervous system